2008
DOI: 10.1016/j.taap.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Phototoxicity and cytotoxicity of fullerol in human lens epithelial cells

Abstract: The water-soluble, hydroxylated fullerene [fullerol, nano-C 60 (OH) [22][23][24][25][26] ] has several clinical applications including use as a drug carrier to bypass the blood ocular barriers. We have assessed fullerol's potential ocular toxicity by measuring its cytotoxicity and phototoxicity induced by UVA and visible light in vitro with human lens epithelial cells (HLE B-3). Accumulation of nano-C 60 (OH) [22][23][24][25][26] in the cells was confirmed spectrophotometrically at 405 nm and cell viability es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 47 publications
1
69
0
1
Order By: Relevance
“…[58][59][60][61] Before evaluating the therapeutic utility of fullerol, we wanted to define the therapeutic window of dose availability for our studies using NP cells. Upon performing a dose-dependent LDH cytotoxicity assay as a measure of toxicity, we observed no apparent cytotoxicity up to 10 µM, tenfold higher than what we chose for our studies (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60][61] Before evaluating the therapeutic utility of fullerol, we wanted to define the therapeutic window of dose availability for our studies using NP cells. Upon performing a dose-dependent LDH cytotoxicity assay as a measure of toxicity, we observed no apparent cytotoxicity up to 10 µM, tenfold higher than what we chose for our studies (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, similar negative effects to ours were obtained by Fernández-Bedmar and Alonso-Moraga [15]when HL60 cells were treated with this carotenoid. Roberts et al [69] demonstrated that when the human lens epithelial cells (HLE B-3) were pretreated with lutein (20 µM added 2 h prior to irradiation with UVA), the singlet oxygen quencher-lutein significantly protected against fullerol photodamage, phototoxic damage decreased by half.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydroascorbic acid did not show cytotoxicity in our studies at 0.7 mM, but Park et al [72] informed that L-ascorbic acid (the reduced form of dehydroascorbic acid) showed cytotoxicity and induces apoptosis of malignant cells (HL60, NB4 and NB4-R1) in vitro, when they used higher concentrations than ours (0.25-1 mM). Moreover, dehydroascorbic acid (0.5-1 mM) was tested for its protective effect against phototoxic damage induced by fullerol, resulting in some activity against metabolic damage [69].…”
Section: Discussionmentioning
confidence: 99%
“…3 For instance, hypoxia does not regulate human ESC proliferation, but it has been shown to be critical for their differentiation into cardiac cells, mainly triggered under hypoxic conditions. 5 Yang et al, 6 showed that differentiation of myoblasts is favoured in a hypoxic microenvironment, with undifferentiated myoblasts presenting high levels of HIF1α, whereas differentiated myoblasts express high levels of HIF2α . The study by Kudová et al, 9 showed that HIF-1α deficiency significantly impaired the transcription of cardiac cell specific genes, and therefore the differentiation of ESCs into cardiomyocytes.…”
Section: Effect Of Oxygen Content On In Vitro Stem Cell Differentiationmentioning
confidence: 99%